Preparation method of high-strength antibacterial glaze
By adding silver/europe hydroxyapatite and scandium oxide to the glaze, combined with the synergistic antibacterial effects of silver ions and europium ions, the problem of insufficient strength of existing antibacterial ceramic glaze is solved, and efficient antibacterial performance and strength are achieved Improve and prepare glaze with high antibacterial rate and high strength.
Patent Information
- Application Number
- CN202411369949.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2024-12-27
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing antibacterial ceramic glazes have not effectively improved the strength of the glaze while improving the antibacterial properties, making it difficult to meet the needs for high-strength and long-term antibacterial properties.
By adding silver/europe hydroxyapatite to the glaze and combining crystals generated by scandium sintering, the antibacterial properties and strength of the glaze are enhanced, and the synergistic antibacterial effects of silver ions and europium ions are used to enhance the bactericidal ability of the glaze is enhanced by using the synergistic antibacterial effects of silver ions and europium ions to enhance the bactericidal ability of the glaze. , and improve the density and hardness of the glaze through ball milling and ultrasonic dispersion techniques.
The prepared high-strength antibacterial glaze not only has excellent antibacterial properties, with an antibacterial rate of up to 99.9%, but also significantly improves the bending strength and hardness. It can maintain the bactericidal effect for a long time and exhibit high strength in mechanical properties. and wear resistance.
Smart Images

Figure CN119191710A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of glazes, in particular to a method for preparing a high-strength antibacterial glaze. Background Art
[0002] With the progress of society and the continuous improvement of people's living standards, people's health awareness has been continuously enhanced. In recent years, due to the widespread use of antibacterial ceramics in people's daily lives, it has attracted more and more attention. Therefore, research on improving the antibacterial properties of glazes has become one of the hot topics of researchers.
[0003] Apatite is a general term for various phosphates, which has good chemical stability and biocompatibility, no side effects on the human body, and is widely used in the fields of medical treatment, coatings, etc. For example, the patent application publication number CN 114436532 A discloses an antibacterial self-cleaning ceramic glaze and ceramic tableware with antibacterial self-cleaning function. The glaze of the invention fixes silver or its particles on apatite, calcium phosphate, zirconium phosphate, clay minerals and other carriers to prepare an antibacterial self-cleaning ceramic glaze, and its antibacterial effect can reach more than 99%, but the strength of the glaze is not improved. Summary of the invention
[0004] 1. Technical issues to be solved
[0005] In view of the shortcomings of the prior art, the present invention provides a method for preparing a high-strength antibacterial glaze. The antibacterial property of the glaze is improved by adding silver / europium hydroxyapatite to the glaze, and the strength of the glaze is improved by utilizing crystals produced by sintering scandium oxide. The glaze prepared by the present invention has good antibacterial property and high strength.
[0006] (II) Technical solution
[0007] A method for preparing a high-strength antibacterial glaze, the preparation method comprising:
[0008] Silver / europium-loaded hydroxyapatite is added to the base glaze for ultrasonic dispersion, and then alumina balls and deionized water are added thereto, ground for 2-4 hours, passed through a 200-250 mesh sieve, and iron is removed to obtain a high-strength antibacterial glaze.
[0009] Furthermore, the mass ratio of the base glaze, silver / europium-loaded hydroxyapatite, alumina balls, and deionized water is 10:0.5-1:30-35:10-15.
[0010] Furthermore, the preparation method of the basic glaze is:
[0011] Add diatomaceous earth, quartz, albite, talc, potassium feldspar, scandium oxide and zinc oxide into a planetary ball mill, ball mill for 20-40 minutes, and pass through a 200-300 mesh sieve to obtain a basic glaze.
[0012] Furthermore, the chemical composition of the basic glaze is 50-66% SiO2, 8-14% Al2O3, 2-5% Na2O, 5-10% CaO, 1-2% Li2O, 0.5-1.5% K2O, 1-2% MgO, 2-5% BaO, 2-4% ZrO2, 0.1-0.5% TiO2, 3-8% ZnO, 0.1-0.4% Fe2O3, and 2-10% Sc2O3.
[0013] Furthermore, the preparation method of the silver / europium loaded hydroxyapatite is:
[0014] Add ammonium dihydrogen phosphate to deionized water, use ammonia water to control the pH to 10, stir and mix evenly to obtain liquid A; add calcium nitrate, silver nitrate, europium nitrate, and a surfactant to deionized water, stir and mix evenly to obtain liquid B, add liquid B to liquid A at 90-100°C, use ammonia water to control the pH to 10, stir and react for 2-4 hours, and after completion, let stand, wash with deionized water, and dry to obtain silver / europium hydroxyapatite.
[0015] Furthermore, the concentration of the ammonia water is 50%.
[0016] Furthermore, the surfactant is sodium dodecylbenzene sulfonate.
[0017] Furthermore, the mass ratio of the diammonium phosphate, calcium nitrate, silver nitrate, europium nitrate and surfactant is 10:2-4:1-2:1-2:0.1-0.2.
[0018] (III) Beneficial technical effects
[0019] The present invention uses ammonium dihydrogen phosphate, silver nitrate, europium nitrate, etc. as raw materials, and loads silver ions and europium ions to hydroxyapatite to obtain silver-loaded / europium hydroxyapatite. By adding scandium oxide, silver-loaded / europium hydroxyapatite and other ball milling to the base glaze, sieving, a high-strength antibacterial glaze is obtained. The silver-loaded / europium hydroxyapatite prepared by the present invention contains double antibacterial particles, i.e., silver ions and europium ions, wherein the europium ions can hinder the synthesis of peptidoglycan, combine with the internal protein of bacterial cells, destroy the bacterial structure, and make the bacteria lose their original function, achieving the effect of killing bacteria. Silver ions can be adsorbed on the negatively charged cell membrane by Coulomb force, penetrate the cell wall to enter the cell, and the silver ions react with sulfhydryl groups to coagulate the protein, destroy the activity of cell synthase, and the cell loses the ability to divide and dies, achieving the antibacterial effect. And the silver ions and europium ions therein are freed after killing the bacteria, and contact with other bacteria again and kill them, and this cycle repeats, so that the silver / europium hydroxyapatite has a strong bactericidal ability for a long time. In addition, since the silver ions and europium ions themselves are easy to agglomerate, the present invention loads them on hydroxyapatite, reduces the degree of agglomeration, increases its dispersion performance, and thus better exerts its antibacterial effect. The present invention utilizes the synergistic antibacterial effect of silver ions and europium ions, introduces them into the glaze to improve the antibacterial performance of the glaze.
[0020] The silver / europium hydroxyapatite prepared by the present invention is a nano short rod particle structure, and the crystal particles produced by the sintering can be filled in the intergranular gaps of K(Si3Al)O8, Na(Si3Al)O8, etc. with the Sc2Si2O7 crystals produced by scandium oxide, so that the density is increased and the hardness is enhanced. When the glaze surface encounters a bend, it can limit and hinder the crack expansion, thereby improving the strength of the glaze. The glaze prepared by the present invention has been confirmed to have good antibacterial properties and high strength through experiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 is a TEM image of Example 1;
[0022] Figure 2 This is the SEM picture of Example 1 after sintering. DETAILED DESCRIPTION
[0023] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0024] Example 1
[0025] (1) Preparation method of silver / europium-loaded hydroxyapatite
[0026] Add 10 g of ammonium dihydrogen phosphate to deionized water, use 50% ammonia water to control the pH to 10, stir and mix evenly to obtain liquid A; add 4 g of calcium nitrate, 1 g of silver nitrate, 1 g of europium nitrate, and 0.1 g of sodium dodecylbenzene sulfonate to deionized water, stir and mix evenly to obtain liquid B, add liquid B to liquid A at 95°C, use 50% ammonia water to control the pH to 10, stir and react for 3 hours, after completion, let stand, wash with deionized water, and dry to obtain silver / europium hydroxyapatite.
[0027] (2) Preparation method of base glaze
[0028] Add diatomaceous earth, quartz, albite, talc, potassium feldspar, scandium oxide and zinc oxide into a planetary ball mill, ball mill for 30 minutes, pass through a 300-mesh sieve to obtain a basic glaze, and control the chemical composition of the basic glaze to be 60% SiO2, 9.6% Al2O3, 2% Na2O, 10% CaO, 2% Li2O, 0.5% K2O, 1% MgO, 5% BaO, 3% ZrO2, 0.5% TiO2, 4% ZnO, 0.4% Fe2O3 and 2% Sc2O3, with a mass proportion of Sc2O3.
[0029] (3) Preparation method of high-strength antibacterial glaze
[0030] 1 g of silver / europium hydroxyapatite was added to 20 g of the base glaze for ultrasonic dispersion, and then 65 g of alumina balls and 25 g of deionized water were added thereto. The mixture was ground for 4 h and passed through a 200-mesh sieve to remove iron to obtain a high-strength antibacterial glaze.
[0031] Example 2
[0032] (1) Preparation method of silver / europium-loaded hydroxyapatite
[0033] Add 10 g of ammonium dihydrogen phosphate to deionized water, use 50% ammonia water to control the pH to 10, stir and mix evenly to obtain liquid A; add 3 g of calcium nitrate, 1.2 g of silver nitrate, 1.3 g of europium nitrate, and 0.2 g of sodium dodecylbenzene sulfonate to deionized water, stir and mix evenly to obtain liquid B, add liquid B to liquid A at 100°C, use 50% ammonia water to control the pH to 10, stir and react for 2 hours, after completion, let stand, wash with deionized water, and dry to obtain silver / europium hydroxyapatite.
[0034] (2) Preparation method of base glaze
[0035] Add diatomaceous earth, quartz, albite, talc, potassium feldspar, scandium oxide and zinc oxide into a planetary ball mill, ball mill for 30 minutes, pass through a 240-mesh sieve to obtain a basic glaze, and control the chemical composition of the basic glaze to be 60.6% SiO2, 14% Al2O3, 4% Na2O, 5.2% CaO, 1% Li2O, 1.5% K2O, 1.5% MgO, 2% BaO, 2% ZrO2, 0.1% TiO2, 4% ZnO, 0.1% Fe2O3, and 4% Sc2O3 by weight.
[0036] (3) Preparation method of high-strength antibacterial glaze
[0037] 1.2 g of silver / europium hydroxyapatite was added to 20 g of the base glaze for ultrasonic dispersion, and then 65 g of alumina balls and 25 g of deionized water were added thereto. The mixture was ground for 4 h and passed through a 250-mesh sieve to remove iron to obtain a high-strength antibacterial glaze.
[0038] Example 3
[0039] (1) Preparation method of silver / europium-loaded hydroxyapatite
[0040] Add 10 g of ammonium dihydrogen phosphate to deionized water, use 50% ammonia water to control the pH to 10, stir and mix evenly to obtain liquid A; add 2 g of calcium nitrate, 1.6 g of silver nitrate, 1.5 g of europium nitrate, and 0.1 g of sodium dodecylbenzene sulfonate to deionized water, stir and mix evenly to obtain liquid B, add liquid B to liquid A at 90°C, use 50% ammonia water to control the pH to 10, stir and react for 4 hours, after completion, let stand, wash with deionized water, and dry to obtain silver / europium hydroxyapatite.
[0041] (2) Preparation method of base glaze
[0042] Add diatomaceous earth, quartz, albite, talc, potassium feldspar, scandium oxide and zinc oxide into a planetary ball mill, ball mill for 20 minutes, pass through a 300-mesh sieve to obtain a basic glaze, and control the chemical composition of the basic glaze to be 66% SiO2, 8% Al2O3, 2% Na2O, 8% CaO, 1% Li2O, 0.5% K2O, 1% MgO, 2% BaO, 2% ZrO2, 0.1% TiO2, 3.3% ZnO, 0.1% Fe2O3, and 6% Sc2O3, with a mass proportion of 8%.
[0043] (3) Preparation method of high-strength antibacterial glaze
[0044] 1.5 g of silver / europium hydroxyapatite was added to 20 g of the base glaze for ultrasonic dispersion, and then 70 g of alumina balls and 20 g of deionized water were added thereto. The mixture was ground for 2 h and passed through a 200-mesh sieve to remove iron to obtain a high-strength antibacterial glaze.
[0045] Example 4
[0046] (1) Preparation method of silver / europium-loaded hydroxyapatite
[0047] Add 10 g of ammonium dihydrogen phosphate to deionized water, use 50% ammonia water to control the pH to 10, stir and mix evenly to obtain liquid A; add 3 g of calcium nitrate, 1.8 g of silver nitrate, 1.8 g of europium nitrate, and 0.1 g of sodium dodecylbenzene sulfonate to deionized water, stir and mix evenly to obtain liquid B, add liquid B to liquid A at 100°C, use 50% ammonia water to control the pH to 10, stir and react for 3 hours, after completion, let stand, wash with deionized water, and dry to obtain silver / europium hydroxyapatite.
[0048] (2) Preparation method of base glaze
[0049] Add diatomaceous earth, quartz, albite, talc, potassium feldspar, scandium oxide and zinc oxide into a planetary ball mill, ball mill for 30 minutes, pass through a 200-mesh sieve to obtain a basic glaze, and control the chemical composition of the basic glaze to be 50% SiO2, 14% Al2O3, 5% Na2O, 10% CaO, 1% Li2O, 0.5% K2O, 2% MgO, 2% BaO, 4% ZrO2, 0.1% TiO2, 3% ZnO, 0.4% Fe2O3, and 8% Sc2O3 by mass.
[0050] (3) Preparation method of high-strength antibacterial glaze
[0051] 1.8 g of silver / europium hydroxyapatite was added to 20 g of the base glaze for ultrasonic dispersion, and then 65 g of alumina balls and 25 g of deionized water were added thereto. The mixture was ground for 3 h and passed through a 200-mesh sieve to remove iron to obtain a high-strength antibacterial glaze.
[0052] Example 5
[0053] (1) Preparation method of silver / europium-loaded hydroxyapatite
[0054] Add 10 g of ammonium dihydrogen phosphate to deionized water, use 50% ammonia water to control the pH to 10, stir and mix evenly to obtain liquid A; add 3 g of calcium nitrate, 2 g of silver nitrate, 2 g of europium nitrate, and 0.15 g of sodium dodecylbenzene sulfonate to deionized water, stir and mix evenly to obtain liquid B, add liquid B to liquid A at 95°C, use 50% ammonia water to control the pH to 10, stir and react for 3 hours, after completion, let stand, wash with deionized water, and dry to obtain silver / europium hydroxyapatite.
[0055] (2) Preparation method of base glaze
[0056] Add diatomaceous earth, quartz, albite, talc, potassium feldspar, scandium oxide and zinc oxide into a planetary ball mill, ball mill for 40 minutes, pass through a 250-mesh sieve to obtain a basic glaze, and control the chemical composition of the basic glaze to be 52.8% SiO2, 10% Al2O3, 3% Na2O, 8% CaO, 1% Li2O, 1% K2O, 2% MgO, 4% BaO, 2% ZrO2, 0.1% TiO2, 6% ZnO, 0.1% Fe2O3 and 10% Sc2O3, by mass.
[0057] (3) Preparation method of high-strength antibacterial glaze
[0058] 2 g of silver / europium hydroxyapatite was added to 20 g of the base glaze for ultrasonic dispersion, and then 60 g of alumina balls and 30 g of deionized water were added thereto. The mixture was ground for 4 h and passed through a 250-mesh sieve to remove iron to obtain a high-strength antibacterial glaze.
[0059] Comparative Example 1
[0060] The preparation method of the glaze provided in this comparative example is substantially the same as that of Example 1, the main difference being that step (1) does not contain silver nitrate.
[0061] Comparative Example 2
[0062] The preparation method of the glaze provided in this comparative example is substantially the same as that of Example 1, with the main difference being that step (1) does not contain europium nitrate.
[0063] Comparative Example 3
[0064] The preparation method of the glaze provided in this comparative example is substantially the same as that of Example 1, the main difference being that scandium oxide is not contained in step (2).
[0065] The glaze is dried to obtain glaze powder, which is placed in a mold with a size of 22mm×16mm and formed at 2.5t pressure. It is made into a glaze block under a pressure of 220MPa using an isostatic press, and sintered at 1000℃ to obtain a sintered glaze block. The glaze block is cut into a cylindrical glaze block with a diameter of 10mm using a plunge grinding method, and then cut into circular specimens with a thickness of 1.5mm using a diamond internal circle cutting machine, flat ground to 1.0mm, and finally polished using a metallographic specimen polishing machine to obtain a specimen plane.
[0066] The bending strength of the glaze was tested using a universal testing machine with a crosshead speed of 0.5 mm / min and a test span of 30 mm.
[0067] The glaze hardness was tested using a Nuno hardness tester with a load of 1 kg and a loading time of 15 s.
[0068] Bending strength / MPa Nuno hardness / HK Example 1 112.8 498.62 Example 2 129.4 508.94 Example 3 138.6 519.73 Example 4 145.3 528.42 Example 5 140.5 526.28 Comparative Example 3 92.36 473.68
[0069] It can be seen from the table that the glaze prepared by the present invention has good strength and hardness, the highest bending strength can reach 145.3MPa, and the maximum hardness can reach 528.42HK.
[0070] The green body was evenly glazed by dipping glaze method, and after drying, it was placed in a microwave muffle furnace. The sintering temperature was 1000°C, the heating rate was controlled at 15°C / min, the holding time was 10min, and the temperature was cooled with the furnace to obtain a sample.
[0071] Referring to JC / T897-2002, the bactericidal rate of the test sample was tested, and the test strain was Escherichia coli.
[0072] Antibacterial rate / % Example 1 84.6 Example 2 95.0 Example 3 99.5 Example 4 99.9 Example 5 99.9 Comparative Example 1 67.4 Comparative Example 2 70.8
[0073] It can be seen from the table that the glaze prepared by the present invention has excellent antibacterial effect, and the antibacterial rate can reach up to 99.9%.
[0074] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. Such modifications or replacements will not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a high-strength antibacterial glaze, characterized in that: The preparation method is: Silver / europium-loaded hydroxyapatite is added to the base glaze for ultrasonic dispersion, and then alumina balls and deionized water are added thereto, ground for 2-4 hours, passed through a 200-250 mesh sieve, and iron is removed to obtain a high-strength antibacterial glaze.
2. The method for preparing the high-strength antibacterial glaze according to claim 1, characterized in that: The mass ratio of the basic glaze, silver / europium-loaded hydroxyapatite, alumina balls and deionized water is 10:0.5-1:30-35:10-15.
3. The method for preparing the high-strength antibacterial glaze according to claim 1, characterized in that: The preparation method of the basic glaze is: Add diatomaceous earth, quartz, albite, talc, potassium feldspar, scandium oxide and zinc oxide into a planetary ball mill, ball mill for 20-40 minutes, and pass through a 200-300 mesh sieve to obtain a basic glaze.
4. The method for preparing the high-strength antibacterial glaze according to claim 3, characterized in that: The chemical composition of the basic glaze is 50-66% by mass of SiO2, 8-14% by mass of Al2O3, 2-5% by mass of Na2O, 5-10% by mass of CaO, 1-2% by mass of Li2O, 0.5-1.5% by mass of K2O, 1-2% by mass of MgO, 2-5% by mass of BaO, 2-4% by mass of ZrO2, 0.1-0.5% by mass of TiO2, 3-8% by mass of ZnO, 0.1-0.4% by mass of Fe2O3, and 2-10% by mass of Sc2O3.
5. The method for preparing the high-strength antibacterial glaze according to claim 1, characterized in that: The preparation method of the silver / europium-loaded hydroxyapatite is: Add ammonium dihydrogen phosphate to deionized water, use ammonia water to control the pH to 10, stir and mix evenly to obtain liquid A; add calcium nitrate, silver nitrate, europium nitrate, and a surfactant to deionized water, stir and mix evenly to obtain liquid B, add liquid B to liquid A at 90-100°C, use ammonia water to control the pH to 10, stir and react for 2-4 hours, and after completion, let stand, wash with deionized water, and dry to obtain silver / europium hydroxyapatite.
6. The method for preparing the high-strength antibacterial glaze according to claim 5, characterized in that: The concentration of the ammonia water is 50%.
7. The method for preparing the high-strength antibacterial glaze according to claim 5, characterized in that: The surfactant is sodium dodecylbenzene sulfonate.
8. The method for preparing the high-strength antibacterial glaze according to claim 5, characterized in that: The mass ratio of the ammonium dihydrogen phosphate, calcium nitrate, silver nitrate, europium nitrate and surfactant is 10:2-4:1-2:1-2:0.1-0.2.
Citation Information
Patent Citations
Antibacterial self-cleaning ceramic glaze and ceramic tableware with antibacterial self-cleaning function
CN114436532A
Antibacterial ceramic and preparation method thereof
CN112299819A
Antibacterial ceramic glaze and production process thereof
CN116986816A
Potassium feldspar crystal glaze powder for false tooth, preparation method of glaze powder and false tooth
CN117486494A
Glaze
JP1993201747A
Cited By
High-strength antibacterial glaze and preparation process thereof
CN120136432A
